2017
DOI: 10.1371/journal.ppat.1006245
|View full text |Cite
|
Sign up to set email alerts
|

Exosome secretion affects social motility in Trypanosoma brucei

Abstract: Extracellular vesicles (EV) secreted by pathogens function in a variety of biological processes. Here, we demonstrate that in the protozoan parasite Trypanosoma brucei, exosome secretion is induced by stress that affects trans-splicing. Following perturbations in biogenesis of spliced leader RNA, which donates its spliced leader (SL) exon to all mRNAs, or after heat-shock, the SL RNA is exported to the cytoplasm and forms distinct granules, which are then secreted by exosomes. The exosomes are formed in multiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 73 publications
4
106
0
Order By: Relevance
“…As shown Figure 2E (CK1.2-V5, white arrow), CK1.2-V5 is detected in the flagellar pocket (FP), which is important for processes such as exo/endocytosis or flagellum assembly [31]. The FP is also one of the sites of exosome excretion in Trypanosoma brucei [32]. Exosomes are vesicles of endosomal origin released by cells from multi-vesicular bodies into their extracellular environment and known to promote cell-to-cell communications [33].…”
Section: Resultsmentioning
confidence: 99%
“…As shown Figure 2E (CK1.2-V5, white arrow), CK1.2-V5 is detected in the flagellar pocket (FP), which is important for processes such as exo/endocytosis or flagellum assembly [31]. The FP is also one of the sites of exosome excretion in Trypanosoma brucei [32]. Exosomes are vesicles of endosomal origin released by cells from multi-vesicular bodies into their extracellular environment and known to promote cell-to-cell communications [33].…”
Section: Resultsmentioning
confidence: 99%
“…For clarification, in this manuscript, we will refer to all vesicles secreted by prokaryotic microbes as MVs. Similarly to their prokaryote counterparts, eukaryotic microbes also release several types of vesicles, termed extracellular vesicles (EVs), such as exosomes, which originate from the endosomal compartment, and microvesicles, which are shed from the plasma membrane . It has recently been revealed that, in addition to RNA and proteins, vesicles from different eukaryotic systems also harbor DNA molecules.…”
Section: Secreted Vesicles As Dna Freighters and Possible Mediators Omentioning
confidence: 99%
“…Stress conditions are not only able to induce vesicle shedding but also prompt vesicular cargo ‘upgrade’ to facilitate an improved response. One of the greatest challenges confronted by microorganisms is stress induced by antimicrobial treatments, a threat that can be overcome by the development of drug resistance.…”
Section: Vesicular‐dna Release Under Environmental Cuesmentioning
confidence: 99%
“…Studies of Leishmania [30,31], Trypanosoma brucei [32,33] and Plasmodium [34] have clearly shown that these parasites also produce microvesicles that are released into the intercellular space or the bloodstream. Exosomes secreted by P. falciparum are directly related to the infection of red blood cells in a mechanism that seems to be important for the parasite's transmission to the insect vector [34].…”
Section: Exosomes In the Protozoan Trypanosoma Cruzimentioning
confidence: 99%